The Lion King [videorecording (Blu-Ray + DVD)] - Nathanson, Jeff; Zimmer, Hans; Rice, Tim, 1944-; John, Elton; Deschanel, Caleb, 1944- (Disney Blu-ray., 2019)
Simba idolizes his father, King Mufasa, and takes to heart his own royal destiny. But not everyone in the kingdom celebrates the new cub's arrival. Scar, Mufasa's brother, and former heir to the throne, has plans of his own.